1992
DOI: 10.1002/bit.260401106
|View full text |Cite
|
Sign up to set email alerts
|

Protein immobilization to alumina supports: II. Papain immobilization to alumina via organophosphate linkers

Abstract: Particulate aluminum oxides (alumina) were examined as supports for the immobilization of the proteolytic enzyme papain. Two alumina supports termed C1 and CPC were derivatized using organic phosphate linkers to create free carboxyl groups using a two-step process. Papain binding to these derivatized aluminas was performed using the water soluble carbodiimide 1-ethyl-3-(dimethylaminopropyl) carbodiimide. Reactions were optimal at 10 mM carbodiimide. The immobilized protein showed similar kinetic constants when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Inorganic immobilization supports such as particulate aluminum oxides (alumina) have also been examined for immobilization of the proteolytic enzyme, papain [118]. In this research, organic phosphate linkers have been used for creation of free carboxyl groups in a two-step process.…”
Section: Immobilization Of Digestive Enzymes Onto Solid Supportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inorganic immobilization supports such as particulate aluminum oxides (alumina) have also been examined for immobilization of the proteolytic enzyme, papain [118]. In this research, organic phosphate linkers have been used for creation of free carboxyl groups in a two-step process.…”
Section: Immobilization Of Digestive Enzymes Onto Solid Supportsmentioning
confidence: 99%
“…It has been shown that immobilized papain had similar kinetic constants compared to papain in solution. By fluorescence measurements, it was concluded that the hydrophobic environment of the active site remained unchanged, while the structure of the rest of the protein was perturbed by its association with the negatively charged surface [118].…”
Section: Immobilization Of Digestive Enzymes Onto Solid Supportsmentioning
confidence: 99%
“…Several strategies have been devised for enhancing the stability and activity of enzymes in organic media, such as chemical modification, 3 immobilization, 4,5 molecular imprinting with substrates, 6 the addition of effectors, 7 and the use of surfactants. 8,9 Substantial attention has been devoted to the covalent immobilization of enzymes to porous, insoluble supports such as glass, 10 alumina, 11 silica, 11 and chitosan [12][13][14][15][16][17][18][19][20][21] because they possess a high catalytic activity per unit volume of the catalyst and minimum diffusion limitations and facilitate the diffusion of large substrate molecules into the porous structure of the matrix within which enzymes are bound.…”
Section: Introductionmentioning
confidence: 99%
“…Papain has known to work effectively when immobilized in other different supports like on SiO 2 particles containing amine groups [8], alumina [9], nitrilon fiber carrier [10], and water soluble polymer polyvinyl alcohol [11]. Additionally, it is expected that an aerosol spray with formulated papain in pectin gel would not cause any drip.…”
Section: Introductionmentioning
confidence: 99%
“…In weight/volume terms, the enzyme preparations are seldom pure and it is expected that the enzyme source will be used in amounts from 0.001% by weight to 20% by weight formulation. Precise amounts will vary with purity of the enzyme [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%